FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Himmy, Istajib Kulla (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
This study examines company size, liquidity and asset structure on capital structure in the food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the period 2011-2015. Analysis was carried out using multiple linear regression. The test results show that for liquidity variables affect the capital structure, this shows that companies that have high liquidity, will choose to use funding from internal sources first, namely using their current assets rather than having to use funding through debt. These findings support the Pecking Order Theory which states that companies will prefer to use internal funding, namely by using their current assets to meet their funding needs. Test results for company size and asset structure show no effect on capital structure.